Prevalence Analysis of Hypodermal Infectious and Haematopoetic Necrosis Virus (IHHNV) in Vaname Shrimp (Litopenaeus vannamei) in Bengkalis District - Fahmi, Adzra Ariesta; Feliatra, Feli; Effendi, Irwan; Muhson, Nanang (Journal of Coastal and Ocean Sciences, 2022)
The disease is a limiting factor and causes economic losses in the cultivation of white shrimp (Litopenaeus vannamei). Diseases in vaname shrimp are caused by viruses, microbes, parasites, organisms, and natural conditions. One of these diseases is infectious hypodermal and hematopoietic necrosis (IHHNV). This study was conducted from February to April 2022. This study aimed to analyze the prevalence of IHHNV that attacks white shrimp in the Bengkalis Regency and to observe and observe clinical symptoms in whitewashed shrimp infected with IHHNV in the pond area of the Bengkalis Regency. The research method used in this study is a survey method. The primary data taken included water quality observations, morphological observations, sampling, and detection of IHHNV using the polymerase chain reaction (PCR) method. The results showed that the prevalence of IHHNV in white shrimp was 0%. PCR testing using a specific primer measuring 392bp showed that white shrimp samples from three locations in Bengkalis District, namely Bengkalis District, Bukit Batu District, and Rupat District, were negative for IHHNV and did not show any clinical symptoms of IHHNV on morphological examination